PENGEMBANGAN MODUL PEMBELAJARAN IPA BERBASIS PENDEKATAN KETERAMPILAN PROSES SAINS PADA MATERI LISTRIK DINAMIS UNTUK SISWA KELAS IX MTs AL MUTTAQIN BUPER JAYAPURA - MASKHULIAH, PRIHATEN; BUNGKANG, YUSUF (Jurnal Ilmu Pendidikan Indonesia, 2018)
Research and development ( R & D) about study use module nature of science base on skill approach process science aim to that is: (1) Knowing the way development module at study nature of science. (2) Knowing elegibility from development module at study nature of science. (3) Knowing effectiveness module at study nature of science. (4) Knowing excess and insuffiency module at study nature of science. Analyse data use analysis SPSS 21 to know and reliability validity analysis, descriptive of percentage, normality, different test (test-t) and homogeneity. Result of analysis n-Gain mean of result learning the experiment class 0,73 high concept domination category and the class control 0,65 domination category conception medium. Result of final analysis use SPSS 21 for test-t got by result T calculate ( 3,384) > T tables of ( 1,686), hence is ha refused by its meaning there is domination difference conception between experiment class taught use module nature of science base on skill approach process science with control class which is not taught to use module nature of science base on skill approach process science. Result of mean assess descriptive analysis for the skill process science from plan study execution 1-3 that is assess 3 good category and 4 category very good, so that the skill process effective science used in study.